2018
DOI: 10.37358/mp.18.3.5017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of AML-VAL Nanoparticles as Combined Therapy in Cardiovascular Disease

Abstract: The main aim of this study was to investigate a mixture of two poorly water-soluble active pharmaceutical ingredients (APIs): an angiotensin II receptor antagonist (valsartan) and a calcium channel blocker (amlodipine besylate), chosen in a fixed-dose, in order to obtain new polymeric nanoparticles (NPs) for cardiovascular diseases treatment. NPs were prepared via nanoprecipitation method using poly (D,L-lactide-co-glycolide) (PLGA) as matrix and Pluronic F127 as stabilizer. Three formulations were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 17 publications
1
6
1
Order By: Relevance
“…A mixture of two cardiovascular drugs-valsartan (an angiotensin II receptor antagonist drug) and amlodipine besylate (a calcium channel blocker)-was loaded in polymeric nanoparticles. The formulation of PLGA NPs loaded with valsartan-amlodipine (PLGA:valsartan:amlodipine besylate = 10:16:1) was established in prevoius studies [8,9] as optimal having high EE (%) for both drugs (91.98 ± 0.18% for valsartan and 82.54 ± 0.12% for amlodipine besylate, nano-metric particle size (140.4 ± 1.34 nm) and narrow dispersity (polydispersity index = 0.108 ± 0.03). The cellular uptake of polymeric nanoparticles was investigated by incubating adherent mouse embryo fibroblasts (NIH 3T3) with a suspension of PLGA NPs loaded with valsartanamlodipine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A mixture of two cardiovascular drugs-valsartan (an angiotensin II receptor antagonist drug) and amlodipine besylate (a calcium channel blocker)-was loaded in polymeric nanoparticles. The formulation of PLGA NPs loaded with valsartan-amlodipine (PLGA:valsartan:amlodipine besylate = 10:16:1) was established in prevoius studies [8,9] as optimal having high EE (%) for both drugs (91.98 ± 0.18% for valsartan and 82.54 ± 0.12% for amlodipine besylate, nano-metric particle size (140.4 ± 1.34 nm) and narrow dispersity (polydispersity index = 0.108 ± 0.03). The cellular uptake of polymeric nanoparticles was investigated by incubating adherent mouse embryo fibroblasts (NIH 3T3) with a suspension of PLGA NPs loaded with valsartanamlodipine.…”
Section: Resultsmentioning
confidence: 99%
“…PLGA NPs loaded with valsartan-amlodipine were synthesized via nanoprecipitation method according to previous reports [8,9]. Briefly, PLGA and cardiovascular drugs were dissolved in acetone (organic phase), while Pluronic-F127 was dissolved in distilled water (aqueous phase).…”
Section: Preparation Of Plga Nps Loaded With Valsartan-amlodipinementioning
confidence: 99%
“…PLGA nanoparticles loaded with AML-VAL were prepared by nanoprecipitation method as described elsewhere [19,20] using PLGA, as biodegradable polymeric and an amphiphilic block copolymer -Pluronic F127 as stabilizer. The composition of prepared PLGA nanoparticles loaded with AML-VAL is presented in Table 1.…”
Section: Preparation Of Plga Nanoparticles Loaded With Amlodipine-valsartanmentioning
confidence: 99%
“…In previous studies we evaluated several nanoformulations with different quantities of PLGA and we concluded that in the range of concentrations 5-60 mg PLGA and at a stirring rate of 1200-1500 rpm cardiovascular drugs loaded nanoparticles with good features can be obtained [19,20]. However, the release behavior has only been studied for the nanoformulations with 5, 7.5 and 10 mg PLGA [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation